Community health agent’s work in control of hansens’ disease - Olga Maria de Alencar; Jorg Heukelbach; Thayza Miranda Pereira; Jaqueline Caracas Barbosa (Rev Rene)
The objective of this study is to describe the working process of the Community Health Agents (CHA) as they monitor people with Hansen’s disease. The CHA is a relatively new profession with only playing field in the Unified Health System and focus on disease prevention and health promotion. It is a quantitative study (n = 331), held in Maranhão, Pará, Tocantins and Piaui, between August/2009 and July/ 2010. Data were analyzed with the program EPI-INFO. The results were: 93% of the Community Health Agents are women, mean age 25 years. 84.2% / of the Community Health Agents has completed high school. 87.1% accompanying Hansen’s disease cases. 55.3% use any tool to record cases. 82.2% refer suspected cases to the basic health unit. 43.0% offer on Hansen’s disease. 53.2% of the CHA have training in the disease. The group is predominantly young adult women with secondary education. The study found that despite the low availability of training in control actions of Hansen’s disease, the CHA monitor patients in their territory.